Case report: therapeuthic approach in risperidone induced hyperprolactinemia - Mucha, Argjent; Volkanovska Ilijevska, Cvetanka; Zhivkovich, Marija; Jovanovska Todorova, Biljana (University Clinic of Endocrinology, Diabetes and Metabolic Disorders, Medical Faculty, University “Ss. Cyril and Methodius” - Skopje, 2022)
A 19-year-old female patient with disturbed menstrual cycles caused by chronic use of risperidone and worsening of her psychological state after the introduction of a dopamine agonist. The 17-year-old patient was diagnosed with dissociative conversion disorder. Therefore, she was placed on therapy with risperidone and lamotrigine. After the introduction of the antipsychotic therapy, the menstrual cycles became irregular. Hormonal studies confirmed high prolactin values of 2226 mIU/ml (40-530), and magnetic resonance (MR) confirmed a pituitary adenoma measuring 4 mm. Therefore, the gynecologist introduced therapy with the dopamine agonist cabergoline, 0.5 mg weekly dose. After a short period, the patient’s psychological state became destabilized, with an irritable, aggressive mood, which was followed by consultations with psychiatrists and frequent changes in antipsychotic therapy. After one year, the antipsychotic aripiprazole was introduced together with valproic acid and lorazepam. After two months, the patient noticed a significant improvement in behavior and mood. In the interim, the dose of cabergoline was reduced to 0.25 mg. The patient was referred to our clinic. Control prolactin values were low and cabergoline was discontinued. And the control MRI of the pituitary gland did not confirm the presence of a microadenoma. Discussion and conclusion: The clinical presentation of hyperprolactinemia affects the therapeutic strategy. Asymptomatic hyperpolactinemia should not be medically treated. In case of long-standing hyperprolactinemia, a pituitary adenoma may appear. Dopamine agonist treatment is risky because it may worsen the psychiatric condition as in our case. There are two strategic approaches in antipsychotic-induced hyperprolactinemia: therapy with combined oral contraceptives or treatment with aripiprazole, an antipsychotic that has a dual effect on D2 receptors (agonist/antagonist). Aripiprazole is an antipsychotic that does not cause hyperprolactinemia.
Keywords: hyperprolactinemia; antipsychotic drugs